A Memorable Class Experience (Comparative & International Education Series, 2022)
I am a native of Ghana in West Africa. My current institution is University of Ghana, a public higher education institution situated in Accra, the capital city of Ghana in the West African sub-region. The country that my most   memorable class experience occurred in is the United States of America, where I had been freshly admitted as a Fulbright international graduate student at a research university located in the Midwest. As an international student then, I had this unforgettable experience with a colleague in class and it has impacted me ever since. This incident happened during the first semester of my graduate program. The class colleague involved in this narrative was a Caucasian American, who I later learnt had not travelled to West Africa or any other African country.